Comparison of surface modification chemistries in mouse, porcine, and human islets. Issue 3 (24th May 2014) - SoRelle, Jeffrey A.; Kanak, Mazhar A.; Itoh, Takeshi; Horton, Joshua M.; Naziruddin, Bashoo; Kane, Robert R.
Abstract Beta cell replacement therapy, the transplantation of isolated pancreatic islets by intraportal infusion, offers patients with brittle type 1 diabetes blood glucose regulation with a minimally invasive technique. Chemical modification of islets prior to transplantation, providing a nanothin barrier that potentially includes active protective compounds, has been proposed as a strategy to minimize the inflammatory and immune reactions that often significantly limit graft function and duration. Chemical modification also has the potential to allow the use of alternative sources of islets, such as porcine islets, for transplantation. This investigation compared three orthogonal covalent islet modification techniques across three species (human, porcine, and murine), using multiple measures to determine biocompatibility and effectiveness. All three conjugation chemistries were well tolerated, and the overall efficiency, gross uniformity, and stability of the surface modifications were dependent upon the conjugation chemistry as well as the islet source (human, porcine, or murine). Notably, the reductive modification of surface disulfides was shown to afford intense and long‐lasting modification of human islets. This study demonstrates that murine, human, and porcine islets tolerate a variety of covalent modifications, that these modifications are relatively stable, and that the murine islet model may not be predictive for some chemical contexts. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 869–877, 2015.